The Relationship Between Pediatric Gut Microbiota and SARS-CoV-2 Infection - Romani, Lorenza; Del Chierico, Federica; Macari, Gabriele; Pane, Stefania; Ristori, Maria Vittoria; Guarrasi, Valerio; Gardini, Simone; Pascucci, Giuseppe Rubens; Cotugno, Nicola; Perno, Carlo Federico; Rossi, Paolo; Villani, Alberto; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
This is the first study on gut microbiota (GM) in children affected by COVID-19. Stool samples from 88 patients with suspected SARS-CoV-2 infection and 95 healthy subjects were collected (admission, 3-7 days, discharge) to study GM profile by 16S rRNA gene sequencing and relationship to disease severity. The study group was divided in COVID-19 (68), Non COVID-19 (16) and MIS-C (4). Correlations amongst GM ecology, predicted functions, multiple machine learning (ML) models and inflammatory response were provided for COVID-19 and Non COVID cohorts. The GM of COVID-19 cohort resulted dysbiotic, with the lowest α-diversity compared to Non COVID and CTRLs and by a specific β-diversity. Its profile appeared enriched in Faecalibacterium, Fusobacterium, Neisseria and reduced in Bifidobacterium, Blautia, Ruminococcus, Collinsella, Coprococcus, Eggerthella, Akkermansia, compared to CTRLs (p<0.05). All GM paired-comparisons disclosed comparable results through all time-points. The comparison between COVID-19 and Non COVI-19 cohorts highlighted a reduction of Abiotrophia in the COVID-19 cohort (p<0.05). The GM of MIS-C cohort was characterized by an increase of Veillonella, Clostridium, Dialister, Ruminococcus, Streptococcus, and a decrease of Bifidobacterium, Blautia, Granulicatella, Prevotella, compared with CTRLs. Stratifying for disease severity, the GM associated to “moderate” COVID-19 was characterized by lower -diversity compared to “mild” and “asymptomatic” and by a GM profile deprived in Neisseria, Lachnospira, Streptococcus and Prevotella and enriched in Dialister, Acidaminococcus, Oscillospora, Ruminococcus, Clostridium, Alistipes and Bacteroides. The ML models identified Staphylococcus, Anaerostipes, Faecalibacterium, Dorea, Dialister, Streptococcus, Roseburia, Haemophilus, Granulicatella, Gemmiger, Lachnospira, Corynebacterium, Prevotella, Bilophila, Phascolarctobacterium, Oscillospira, Veillonella as microbial markers of COVID-19. The KEGG orthologs (KO)-based prediction of GM functional profile highlighted 28 and 39 KO-associated pathways to COVID-19 and CTRLs, respectively. Finally, Bacteroides and Sutterella correlated with proinflammatory cytokines regardless disease severity. Unlike adult GM profiles, Faecalibacterium was a specific marker of pediatric COVID-19 GM. The durable modification of patients’ GM profile, suggested a prompt GM quenching response to SARS-CoV2 infection since the first symptoms. Faecalibacterium and reduced fatty acid and amino acid degradation were proposed as specific COVID-19 disease traits, possibly associated to restrained severity of SARS-CoV-2 infected children. Altogether, this evidence provides a characterization of the pediatric COVID-19-related GM.